Towards experimental manipulation of stochasticity in gene expression - Viñuelas, José; Kaneko, Gaël; Coulon, Antoine; Beslon, Guillaume; Gandrillon, Olivier (Progress in biophysics and molecular biology, 2012)
For decades, most of molecular biology was driven by the “central dogma” in which the phenotype is defined by the genotype following a fully deterministic point of view. However, during the last 10 years, a wealth of studies has demonstrated that a given genotype can generate multiple phenotypes in identical environmental conditions, mainly because of the inherently probabilistic nature of the transcription process. It has also been shown that cells can tune this variability at the molecular level. Although previously described as a useless “noise”, stochastic gene expression has now been shown by many authors to be an essential part of diverse biological processes. Chromatin dynamics having a central role in higher eukaryotes, we decided to investigate its involvement in the generation and control of stochasticity in gene expression (SGE). Our experiments reveal that the chromatin environment of a gene plays an important role in regulating SGE. Indeed, we find that histone acetylation and DNA methylation significantly affect SGE, suggesting that cells are able to adjust the variability of the expression of their genes through modification of chromatin marks. Given that the alteration of chromatin marks is itself subject to the expression of chromatin modifiers, our results shed light on a complex circular causality with on the one hand, the effect of gene expression on chromatin and on the other hand, the influence of the local chromatin environment of a gene on the dynamics of its expression.